2017
DOI: 10.1177/1474515117695722
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factors associated with self-care behaviors using the COM-B model in patients with chronic heart failure

Abstract: Chinese patients with chronic heart failure have poor self-care behaviors. Factors associated with self-care behaviors are confidence, functional capacity, knowledge, health literacy and social support. Self-care confidence appears to be a mediator between knowledge, health literacy, social support and self-care behaviors. Targeted interventions are required to optimize self-care behaviors in patients with chronic heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
3
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 47 publications
5
80
3
3
Order By: Relevance
“…One possible reason is that patients living with family members have more social support, including emotional support, financial assistance and daily care (Sun et al, ; Wang et al, ; Xie et al, ). Earlier studies revealed that social support from family members was linked to lower readmission and higher medication adherence, whereas a lack of social support and living alone was related to psychosocial distress in HF patients (Chamberlain, ; Zou et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible reason is that patients living with family members have more social support, including emotional support, financial assistance and daily care (Sun et al, ; Wang et al, ; Xie et al, ). Earlier studies revealed that social support from family members was linked to lower readmission and higher medication adherence, whereas a lack of social support and living alone was related to psychosocial distress in HF patients (Chamberlain, ; Zou et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The total score of each subscale is transformed into a centesimal score between 0–100 according to a transform formula from previous studies (Riegel et al, ; Xie et al, ). A score ≥ 70 in each subscale can be used as the cut‐off point to decide self‐care adequacy based on prior studies (Xie et al, ; Zou, Chen, Fang, Zhang, & Fan, ). The schfi v. 6.2 has been translated into Chinese, and its psychometric properties have been confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of all 20 studies included in this review are detailed in Table 2. Most of the studies were published in the United States (n = 13) (Brega et al, 2012;Chen, 2014;Cho, Lee, Arozullah, & Crittenden, 2008;Como, 2018;Crook et al, 2016;Guo et al, 2014;Hickman, Clochesy, & Alaamri, 2016;Jin, Lee, & Dia, 2019;Osborn, Cavanaugh, et al, 2011;Osborn, Cavanaugh, Wallston, & Rothman, 2010;Osborn, Paasche-Orlow, Bailey, & Wolf, 2011;Schillinger, Barton, Karter, Wang, & Adler, 2006;Soones et al, 2017), with the remaining studies published in China (n = 2) (Sun et al, 2013;Zou, Chen, Fang, Zhang, & Fan, 2017), Taiwan (n = 2) (Hou et al, 2018; Y. J. , Thailand (n = 2) (Intarakamhang & Intarakamhang, 2017;Photharos, Wacharasin, & Duongpaeng, 2018), and South Korea (n = 1) (E. H. Lee, Lee, & Moon, 2016). Study designs included cross-sectional (n = 19) (Brega et al, 2012;Chen, 2014;Cho et al, 2008;Como, 2018;Crook et al, 2016;Guo et al, 2014;Hickman et al, 2016;Hou et al, 2018;Jin et al, 2019;E.…”
Section: Overview Of Studies Includedmentioning
confidence: 99%
“…H. Lee et al, 2016; Y. J. Osborn, Cavanaugh, et al, 2011;Osborn et al, 2010;Osborn, Paasche-Orlow, et al, 2011;Photharos et al, 2018;Schillinger et al, 2006;Soones et al, 2017;Sun et al, 2013;Zou et al, 2017) and mixed methods (n = 1) (Intarakamhang & Intarakamhang, 2017). Sample sizes ranged from 62 to 2,594, with only seven studies calculating sample sizes a priori (Chen, 2014;Como, 2018;Hou et al, 2018;Intarakamhang & Intarakamhang, 2017;E.…”
Section: Overview Of Studies Includedmentioning
confidence: 99%
“…However, they may lack knowledge on how to monitor and interpret their symptoms, as well as when and where to seek treatment. In addition, they may have limited access to HF services that aid them to actively engage in self-care [10,11]. A scientific statement from the American Heart Association for healthcare professionals (HCP) presents technology as a promising way to support patients' self-care and encourages HCPs to have an active role in the development and use of technology to improve active patient and HCP engagement in patient self-care [12].…”
Section: Introductionmentioning
confidence: 99%